2019
DOI: 10.1002/jaoc.12069
|View full text |Cite
|
Sign up to set email alerts
|

Personality, Motivation, and Internet Gaming Disorder: Conceptualizing the Gamer

Abstract: Using a group correlational design and path analysis, the authors examined the relationships among personality, motivation, and internet gaming disorder (IGD). Findings showed that significant predictors of IGD included male gender, neurotic and introverted personality traits, and motivation related to achievement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 45 publications
5
32
0
3
Order By: Relevance
“…However, dysregulated gaming can lead to addiction-like symptoms. A systematic literature review on IGD by Paulus et al showed that IGD may be observed up to ve times more often in male children than in female children [7], and the present study showed that male gender is an important predictor of IGD, a nding that was reported across several studies [8,17,18,19,20,21,22,23]. Moreover, free time activities of 'high risk' participants were more related to screen time activities than non-screen time activities when compared to 'low risk' participants.…”
Section: Discussionsupporting
confidence: 79%
“…However, dysregulated gaming can lead to addiction-like symptoms. A systematic literature review on IGD by Paulus et al showed that IGD may be observed up to ve times more often in male children than in female children [7], and the present study showed that male gender is an important predictor of IGD, a nding that was reported across several studies [8,17,18,19,20,21,22,23]. Moreover, free time activities of 'high risk' participants were more related to screen time activities than non-screen time activities when compared to 'low risk' participants.…”
Section: Discussionsupporting
confidence: 79%
“…Though relatively small, the significant direct association between social anxiety and IGD suggests that symptoms of social anxiety (like fear of talking to strangers and avoidance of social situations) may represent a risk factor for IGD. In line with this view, it has been shown that gamers may tend to avoid the inadequacy felt in the offline world by creating a different and more confident online social self (Allison, von Wahlde, Shockley, & Gabbard, 2006;Carlisle, Neukrug, Pribesh, & Krahwinkel, 2019). However, as the virtual world is progressively perceived as safer, the devotion to the online world and activities increases and may result in the escalation of some IGD symptoms, such as loss of nongaming interest and/or jeopardized daily life activities (school, job, family), especially for gamers holding a poor offline selfconcept (e.g., Dieter et al, 2015).…”
Section: Discussionmentioning
confidence: 86%
“…In line with this view, it has been shown that gamers may tend to avoid the inadequacy felt in the offline world by creating a different and more confident online social self (Allison, von Wahlde, Shockley, & Gabbard, 2006;Carlisle, Neukrug, Pribesh, & Krahwinkel, 2019). However, as the virtual world is progressively perceived as safer, the devotion to the online world and activities increases and may result in the escalation of some IGD symptoms, such as loss of nongaming interest and/or jeopardized daily life activities (school, job, family), especially for gamers holding a poor offline selfconcept (e.g., Dieter et al, 2015). These arguments have been also supported by researchers who described the "social experience" of gaming as unique and crucial in the explanation of IGD (Carlisle et al, 2019, p. 108).…”
Section: Discussionmentioning
confidence: 86%
“…Los predictores fundamentales de dicho trastorno incluyen rasgos de la personalidad neurótica e introvertida, y la motivación relacionada con los logros (Carlisle et al, 2019). También cuenta con una mayor proporción en el género masculino (Fam, 2018), ya que suelen jugar mucho más a los videojuegos (Dong et al, 2018), con una relación de hombres y mujeres de 3:1 (Dong et al, 2018;Wang et al, 2019).…”
Section: Revisión De La Literaturaunclassified